Marginalized female in two song lyrics, Tragedi Cinta: textual-metaphoric representations - Purwanto, Sugeng; Nurhamidah, Idha; Rahayu, Endang Yuliani; Soepriatmadji, Liliek; Rustipa, Katharina; Idriz, Mesut (EduLite: Journal of English Education, Literature and Culture, 2023)
Old romantic songs of the 1980s linger; especially for people, at the moment, in their 60s or so. Such songs are rich in moral teaching, applicable in any religion on earth. The current study which examined Benjamin S’ and Ida Royani’s the same song lyrics Tragedi Cinta but of different versions aimed to construe the meanings of both songs viewed from their textual-metaphoric representations. The two song lyrics were analyzed employing a software application UAMCT 6.8, adopting Hallidayan SFL on thematic progression, leading to their modes of the discourse. Also dealt with herein is the use of both grammatical and lexical metaphors to examine how meanings are realized. The findings show that ‘female’ is marginalized in three ways, namely (1) the use of active voice without any attempt to hide the identity for doing sincere things as opposed to ‘male’ put in passive voice to hide the identity for doing bad things, (2) the use of marked themes indicate high literary values employed in both song lyrics, (3) the use of both lexical and grammatical metaphoric styles implies excellently-written song lyrics, and (4) moral teaching of both song lyrics is also highlighted to give evidence of ‘female’ marginalization and it is, thereby recommended to avoid romantic juvenile delinquency, especially of the millennial generation termed as ‘digital natives’ who can get access to abundant information without limit of time and space; no matter how hard the social, religious and familial authorities try to ban the negative impacts of the world’s largest information technology industry.